2016
DOI: 10.1007/s00330-016-4702-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cerebral vasospasm following aneurysmal subarachnoid haemorrhage: a systematic review and meta-analysis

Abstract: • 33.7% of patients with cerebral Vasospasm following aneurysmal subarachnoid-hemorrhage have an unfavorable outcome. • Refractory vasospasm patients treated using endovascular interventions have lower relative risk of unfavourable outcome. • Subarachnoid haemorrhage patients with severe vasospasm may benefit from endovascular interventions. • The relative risk of unfavourable outcome is lower in patients treated with Cilostazol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 91 publications
0
31
0
3
Order By: Relevance
“…A key difference in the current study design, compared to prior literature, is that we adjusted for confounding factors beyond simply selecting for control patients with normal mental status at hospital admission. It is notable that, in the primary analysis, cases had improved unadjusted outcomes and a trend toward improved adjusted outcomes, a finding that is particularly remarkable given that cases had significantly higher rates of delayed cerebral vasospasm, a complication of aSAH typically associated with significantly worse neurologic outcomes . This observation might indicate the presence of protective factors among patients who initially present with “sentinel” or clinically unimpressive symptoms that are not reflected in the typical predictors of outcome following aSAH, perhaps because those aneurysms are more prone to manifest with minor and/or intermittent leakage as opposed to overt rupture.…”
Section: Discussionmentioning
confidence: 96%
“…A key difference in the current study design, compared to prior literature, is that we adjusted for confounding factors beyond simply selecting for control patients with normal mental status at hospital admission. It is notable that, in the primary analysis, cases had improved unadjusted outcomes and a trend toward improved adjusted outcomes, a finding that is particularly remarkable given that cases had significantly higher rates of delayed cerebral vasospasm, a complication of aSAH typically associated with significantly worse neurologic outcomes . This observation might indicate the presence of protective factors among patients who initially present with “sentinel” or clinically unimpressive symptoms that are not reflected in the typical predictors of outcome following aSAH, perhaps because those aneurysms are more prone to manifest with minor and/or intermittent leakage as opposed to overt rupture.…”
Section: Discussionmentioning
confidence: 96%
“…Endovascular intervention is commonly used to chemically (intra-arterial (IA) infusion of vasodilatory agents) or mechanically (balloon angioplasty) ameliorate vasospasm which has been refractory to medical therapy 7. However, since no randomized controlled trial has evaluated the safety and efficacy of endovascular treatment for vasospasm, the current guidelines are based on clinical case series and expert consensus 8. As such, the clinical effect of endovascular vasospasm treatment remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…25 In a systematic review and meta-analysis of 62 studies (26 of them were randomized trials), Boulouis et al concluded that IAT may improve the outcome after severe/refractory vasospasm. 26 They demonstrated overall an unfavorable outcome after sCVS following aneurysmal SAH in 2,490 of 8,976 patients (33.7%), defined as mRS 3 to 6 at last followup. In our study there was an unfavorable outcome after 6 months in 46.1% for sSAH patients with a single IAT and in 40.8% for patients with multiple IATs for sCVS, but we defined an unfavorable outcome as mRS 4 to 6.…”
Section: Discussionmentioning
confidence: 93%